Prealgebra (7th Edition)

Published by Pearson
ISBN 10: 0321955048
ISBN 13: 978-0-32195-504-3

Chapter 4 - Test - Page 325: 26



Work Step by Step

$(-\frac{3}{4})^{2}\div(\frac{2}{3}+\frac{5}{6})$ $=(-\frac{3}{4}\times-\frac{3}{4})\div(\frac{4}{6}+\frac{5}{6})$ $=(\frac{3}{4}\times\frac{3}{4})\div\frac{9}{6}$ $=\frac{9}{16}\div\frac{3}{2}$ $=\frac{9}{16}\times\frac{2}{3}$ $=\frac{3}{8}\times\frac{1}{1}$ $=\frac{3}{8}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.